Peculiarities of Treatment for Chronic Gastritis Associated with Herpesviruses in Children - O.Ye. Abaturov; N.Y. Leonenko (Zaslavsky O.Yu., 2014)
The article presents data on the clinical manifestations and peculiarities of treatment for chronic gastritis associated with viral infections in children.